MANAJEMEN LINGKUNGAN BERBASIS SEKOLAH DALAM PENANAMAN KARAKTER DAN KESADARAN LINGKUNGAN HIDUP BERKELANJUTAN DI SEKOLAH DASAR - Nurlinda Safitri (Jurnal Pendidikan Dasar, 2022)
School-based environmental management in elementary schools is a system that needs to be implemented in an effort to build sustainable character and environmental awareness in schools. This management process consists of planning, organizing, implementing and monitoring. The purpose of this study was to integrate the environmental management process into school stakeholders in elementary schools. This type of research is library research with document study method. The results of this research regarding elementary school-based environmental management can be integrated with school stakeholders in order to create awareness of a sustainable environment.